Outcomes of Infants Who Failed to Extubate despite Systemic Corticosteroids - Cuna, Alain; Lewis, Tamorah; Oschman, Alexandra; Dai, Hong Ying; Brophy, Katie; Norberg, Michael; Nyp, Michael; Truog, William (American Journal of Perinatology, 2017)
Objective The objective of this study was to assess the outcomes of preterm infants who failed to extubate following initial treatment with steroids.Materials and Methods This is a retrospective cohort study of ventilator-dependent preterm infants treated with first course of systemic steroids to facilitate extubation. Outcomes of infants who successfully extubated were compared with infants who failed to extubate.Results In this study, 74 infants (mean gestation 25.4 ± 1.4 weeks and mean birth weight 764 ± 163 g) met inclusion criteria. Of these, 41 (55%) were successfully extubated and 33 (45%) were not. Baseline demographics were similar between the two groups. The primary outcome of severe bronchopulmonary dysplasia (BPD) or death at 36 weeks was higher among infants who failed to extubate (94 vs. 63%, p = 0.002). Severe BPD remained significantly higher even after adjustment for potential confounders (odds ratio: 12.2, 95% confidence interval: 2.1–70.5, p = 0.005). Extubation failure was also associated with substantially higher rate of tracheostomy (32 vs. 5%, p = 0.003) and gastrostomy tube placement (61 vs. 22%, p = 0.001), as well as longer days of hospitalization (179 ± 72 vs. 129 ± 44 days, p = 0.001) and mechanical ventilation (112 ± 89 vs. 52 ± 42 days, p < 0.001).Conclusion Failure to extubate after first course of systemic steroids for BPD is associated with poor prognostic implications.
Keywords: prematurity; bronchopulmonary dysplasia; corticosteroids; extubation; outcome